SCIENTIFIC AND PRACTICAL BASIS FOR THE EFFECTIVENESS OF THE MODERN METHOD OF IRRIGATION (Spectrum Journal of Innovation, Reforms and Development, 2024)
Due to global climate change, the demand for irrigation water is increasing everywhere in the world, in this regard, the available limited water resources are becoming scarce, careful use of the available limited water resources is considered an urgent task of today. A drip irrigation system is an irrigation network designed to deliver the amount of water to the root layer of cotton equal to the plant's water needs. The difference between drip irrigation and other irrigation methods is that the water is supplied evenly across the field according to the needs of the crop. Crop areas of the field are moistened uniformly. Excess moisture does not occur in the soil, the main task of today is to eliminate excess water loss.